PENGEMBANGAN MATHEMATICAL MAPLE BERBASIS KOOPERATIF THINK-PAIR-SHARE UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS MAHASISWA DAN KUALITAS PERKULIAHAN FISIKA MATEMATIK - Tandililing, Edy (Jurnal Pendidikan Matematika dan IPA, 2015)
The main purpose of research is whether the representation of mathematical ability of students increased after learning gained through the program Mathematical Maple combined with cooperative learning Think Pair Share on lectures of Mathematical Physics. Subjects were students of third semester of physical education courses with the number of 35 students. The method used is a Class Action Research conducted through three cycles or actions which each cycle. The research instrument consists of: test, questionnaire, and observation guidelines. Based on data analysis concluded: (1) the ability of the representation of the students in understanding the meaning of the physical, the ability of representation of students to represent the mathematical equation in the form of graphs, the ability of the representation of the students in giving meaning physical on the results of visualization, and the ability of the representation of the students in understanding the course materials Mathematical Physics increase in each cycle or action; (2) the implementation process using computer-aided applications maple in the first cycle having problems because the students have never known the computer-assisted program maple, but in the next cycle students were able to adjust the maple program that is being used; and (3) the response of students to the course of action given the overall increase in each cycle. Keywords: Ability Representation, Think Pair Share.